2008
DOI: 10.1107/s0108270108038778
|View full text |Cite
|
Sign up to set email alerts
|

FourN7-alkoxybenzyl-substituted 4,5,6,7-tetrahydro-1H-pyrazolo[3,4-b]pyridine-5-spiro-1′-cyclohexane-2′,6′-diones: hydrogen-bonded supramolecular structures in zero, one, two or three dimensions

Abstract: 3-tert-Butyl-7-(4-methoxybenzyl)-4',4'-dimethyl-1-phenyl-4,5,6,7-tetrahydro-1H-pyrazolo[3,4-b]pyridine-5-spiro-1'-cyclohexane-2',6'-dione, C(31)H(37)N(3)O(3), (I), 3-tert-butyl-7-(2,3-dimethoxybenzyl)-4',4'-dimethyl-1-phenyl-4,5,6,7-tetrahydro-1H-pyrazolo[3,4-b]pyridine-5-spiro-1'-cyclohexane-2',6'-dione, C(32)H(39)N(3)O(4), (II), 3-tert-butyl-4',4'-dimethyl-7-(3,4-methylenedioxybenzyl)-1-phenyl-4,5,6,7-tetrahydro-1H-pyrazolo[3,4-b]pyridine-5-spiro-1'-cyclohexane-2',6'-dione, C(31)H(35)N(3)O(4), (III), and 3-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…1 and 2). Compounds (I) and (II) are related to the analogues (III) (Cruz et al, 2008) and (IV) (Trilleras et al, 2008) reported earlier, but they differ from these earlier examples in carrying no methyl substituents on the spirocyclohexane ring. Compounds (I) and (II) were synthesized using a straightforward modification of the synthetic method employed earlier (Cruz et al, 2008;Trilleras et al, 2008), using cyclohexane-1,3-dione in place of the 5,5-dimethylcyclohexane-1,3-dione used previously.…”
Section: Commentmentioning
confidence: 69%
See 2 more Smart Citations
“…1 and 2). Compounds (I) and (II) are related to the analogues (III) (Cruz et al, 2008) and (IV) (Trilleras et al, 2008) reported earlier, but they differ from these earlier examples in carrying no methyl substituents on the spirocyclohexane ring. Compounds (I) and (II) were synthesized using a straightforward modification of the synthetic method employed earlier (Cruz et al, 2008;Trilleras et al, 2008), using cyclohexane-1,3-dione in place of the 5,5-dimethylcyclohexane-1,3-dione used previously.…”
Section: Commentmentioning
confidence: 69%
“…In continuation of our structural study of N 7 -benzyl-substituted pyrazolo[3,4-b]pyridine-5-spiro-1 0 -cyclohexane-2 0 ,6 0 -diones (Cruz et al, 2008;Trilleras et al, 2008), itself part of a programme exploring the use of multicomponent condensation reactions, especially those induced by microwave irradiation under solvent-free conditions, for the synthesis of novel heterocycles, we now report the molecular and supramolecular structures of the two title N 7 -benzyl derivatives (Figs. 1 and 2).…”
Section: Commentmentioning
confidence: 93%
See 1 more Smart Citation